Knowledge Improvement of Xerosis Cutis through Health Education in the Elderly - Damayanti; Astindari; Indranarum, Trisiswati; Hadiwidjaja, Farsha Naufal; Axelia, Presstisa Gifta; Hasnikmah Mappamasing (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Xerosis cutis presents in more than 50% of the elderly population and is currently the most common complaint related to a skin condition in the elderly population. However, many of them are still uninformed of this complaint. Education plays an important role in the management of xerosis cutis, such as how to identify and avoid triggering factors and how to break the itch-scratch cycle. Purpose: This study aims to evaluate the level of knowledge on xerosis cutis in the elderly population after receiving health education. Methods: This observational study involved 71 subjects who met the inclusion criteria of being elderly and were willing to participate in this study. The data were collected using questionnaires. The level of knowledge was assessed before and after the health education around xerosis cutis. Result: Eleven (15.49%) male and 60 (84.51%) female subjects participated in this study. There was a significant difference mean scores between the pre-test and post-test after health education (p= <0.001). The means of total scores of the pre-test and post-test were 11.72 ± 1.475 and 12.58 ± 1.662. The questionnaire consisted of  chapters regarding skin changes in the elderly, risk factors for xerosis cutis, and management of xerosis cutis. A significant difference in score between the pre-test and post-test was found in all the chapters (p=0.046, p=0.002, and p=0.006). Conclusion: Following health education, there was an improvement in the elderly's level of knowledge on xerosis cutis.